A further Agnus Dei penny of King Æthelred the Unready. (December 2019) - Keynes, Simon; MacKay, William A.; Naismith, Rory
Abstract : A further example of an Agnus Dei penny recently surfaced at a London auction. 1 It was found in 2018 by a metal-detectorist, in south Lincolnshire. It is the twenty-second recorded example struck from Agnus Dei obverse and reverse dies, and takes the total of surviving specimens, including the two known mules with the Last Short Cross type, to twenty-four. The new coin is well preserved, without piercing, mounting or pecking, but is chipped between two and five o'clock. Both the mint, Leicester, and the moneyer, Æthelwig, are already known for the Agnus Dei type; 2 it is in fact a die-duplicate of the other known coin of Æthelwig. 3 The new coin brings the number of known examples for Leicester to four, and adds a second example for the moneyer. Allowing for the chip, the weight of 1.46g is consistent with the c. 1.75g noted for more complete examples.